Aminophylline Infusion Induced Excretion of Magnesium DuringMagnesium Loading Test in Critically Ill Patients: Aminophylline induced excretion of magnesium - PatientsSeyed Mojtaba Sohrevardi; Mojtaba Mojtahedzadeh (Iranian Journal of Pharmaceutical Sciences, 2007)
The aim of this study was to investigate the prevalence of Mg deficiency and effectof aminophylline infusion on urine magnesium concentration after magnesiumloading test (MLT). To determine serum Mg, venous blood specimens were obtainedjust before the first MLT. Two MLTs were performed. The first one was donebefore starting aminophylline infusion and the 2ndone was done during aminophyllineinfusion. Urine samples were collected from the starting of Mg infusion in each phase.Although low serum Mg was present only in 2 patients, MLTshowed Mg deficiencyin 18 patients. MLTdetected Mg deficiency in 13 out of 14 patients with normalserum Mg, in 2 out of 2 subjects with serum hypomagnesemia, and in 3 out of 5 caseswith serum hypomagnesemia. There was no relationship between Mg retention, ageand serum Mg concentrations. Aminophylline administration increased the 24-h urineMg concentration by 29.3%.